Bootstrap performance with heteroskedasticity - Russell Davidson; Andrea Monticini (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2023)
The aim of this paper is to illustrate more than one instance of poor bootstrap performance, and to see how available diagnostic techniques can indicate reliably when and how this poor performance can arise. Two particular features that seem to be important to explain bootstrap discrepancy are illustrated by some Monte Carlo experiments.
Keywords: C12; C22; C32; 330; Bootstrap inference; fast double bootstrap; conditional fast double bootstrap; heteroskedasticity